Nanowire Networks: Electronic Properties of Complex Self‐Assembled InAs Nanowire Networks (Adv. Electron. Mater. 6/2016). (15th June 2016) - Heedt, Sebastian; Vakulov, Daniil; Rieger, Torsten; Rosenbach, Daniel; Trellenkamp, Stefan; Grützmacher, Detlev; Lepsa, Mihail Ion; Schäpers, Thomas
Abstract : The front cover illustration highlights an array of V‐shaped grooves etched into a silicon (100) substrate, as described by Heedt et al. in article number 1500460. Crystallographic {111} facets are formed and indium arsenide nanowires grow perpendicularly on these facets, merge and form monocrystalline nanowire junctions and complex nanowire networks. These are employed for electronic multi‐terminal devices. The colored branches are an artistic illustration of current paths along the nanowire networks.